Genetic findings in sport-related concussions: potential for individualized medicine? - Jane McDevitt; Evgeny Krynetskiy (Concussion)
Concussion is a traumatic transient disturbance of the brain. In sport, the initial time and severity of concussion is known giving an opportunity for subsequent analysis. Variability in susceptibi...